Psychometric evaluation of the Serbian version of Big Five Questionnaire for Children and development of a short form (SBFQ-C-29) - Popov, Stanislava; Sokić, Jelena; Radović, Danijela (Psihološka istraživanja, 2021)
The personality characteristics of children and adolescents explained by the Big five model are studied much lesser than the personality characteristics of adults. One of the rare self-assessment personality instruments for preadolescent and adolescent age is the Big Five Questionnaire for Children (BFQ-C). The aim of this study was an evaluation and presentation of the metric characteristics of the BFQ-C in the Serbian language. The sample consisted of 881 participants (57% female) who attended the final grades of elementary and initial grades of secondary schools (M=14 years, SD = .99). The original model, previously validated in several European languages, were tested through CFA. The hypothesized model did not obtain satisfactory fit indices, as well as the shorter version of the scale. Following these results, the sample was randomly divided into two datasets, opted for further exploration of the Serbian version of BFQ’s latent structure. The final result is the 29-items questionnaire solution, loaded onto five factors with satisfactory internal consistency, homogeneity, and adequacy, consistent with previous studies addressing different cultures and languages.